Development Of Pizza Base Using Functional Ingredients (PUSA Journal of Hospitality and Applied Sciences, 2020)
Background: Iron deficiency anaemia is a global problem affecting a remarkably high  percentage of people in India. It results in motor and mental impairment in children and poor  work productivity and reproductive performance in adults. Current eating trends indicate that  pizza is one most favorite snack and meal variety for today’s consumer belonging to various  age groups. Developing healthier variety with utilization of functional properties of traditional  ingredients can help in its value addition. Objective: The present study was undertaken  with the objective of developing alternative nutritious product for traditional pizza base.  Methodology: Experimental study was conducted to develop pizza base with amaranth flour  and dehydrated amaranth leaves as the main ingredients. Sensory analysis, Nutritive value  and shelf life was estimated for the developed product. Label designing was done. Results:The final product was made by using amranth flour (33.82%) whole wheat flour (33.82%)  and refined flour (32.35%) The mean score for overall acceptability of the developed product  was 4.6 ± 0.54 for trained and 4.26 ± 0.58 for consumer panel. Nutritive profile of one  serving (70 gram) of the product was energy (290.36 kcal), protein (8.55 g), carbohydrate  (49.19 g), fat (6.08 g), fibre (5.91 g) and iron (5.09 mg). The product had shelf-life of a day.  Conclusion: The study highlighted that the availability and use of the amaranth pizza base  instead of the regular refined flour pizza base, can help in contributing to iron intake and thus  can be a promising product for all age groups.
Keywords: Pizza base; Amaranth Flour; Whole wheat flour; Anaemia